2020
DOI: 10.1109/tbme.2019.2963043
|View full text |Cite
|
Sign up to set email alerts
|

Calcification Assessment of Bioprosthetic Heart Valve Tissues Using an ImprovedIn VitroModel

Abstract: Calcification is a recurrent problem in patients suffering from heart valve disease and it is the main cause of failure in biological heart valve prostheses. The development of reliable calcification tests that consider both the material properties of the prostheses and the fluid composition is of paramount importance for the effective testing and subsequent selection of new cardiovascular implants. In this work, a fast, reliable and highly reproducible method for the assessment of the calcification potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Apoptotic cell fragments provide additional calcium binding sites, further triggering the calcification of the BHV. 13,14 Good cytocompatibility could be beneficial for reducing leaflet calcification. The cytotoxicity assay indicated that there was no cytotoxicity of pLy-GA-Arg, which may be due to the absence of cytotoxic aldehyde residues on the surface of pLy-GA-Arg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptotic cell fragments provide additional calcium binding sites, further triggering the calcification of the BHV. 13,14 Good cytocompatibility could be beneficial for reducing leaflet calcification. The cytotoxicity assay indicated that there was no cytotoxicity of pLy-GA-Arg, which may be due to the absence of cytotoxic aldehyde residues on the surface of pLy-GA-Arg.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Apoptotic cell fragments provide additional calcium binding sites, further triggering the calcification of BHVs. 13,14 Although BHVs are less thrombogenic than MHVs, many studies have reported that thrombosis is still one of the important factors leading to the failure of BHVs. [15][16][17] These defects mentioned above will cause structural valve deterioration, shortening the service life of BHVs.…”
Section: Introductionmentioning
confidence: 99%
“…ECM has many unique advantages, such as good biocompatibility, excellent biomechanical properties, and rich in cell growth factors [ 33 35 ]. However, the immune response caused by ECM, such as DNA, α -Gal epitope, or residual glutaraldehyde [ 36 , 37 ], should not be ignored. Currently, it is not clear whether there is a threshold of Gal epitope stimulation in the immune response of xenotransplantation induced by α -Gal epitope.…”
Section: Discussionmentioning
confidence: 99%
“…ECM has many unique advantages, such as good biocompatibility, excellent biomechanical properties, and rich in cell growth factors [33][34][35]. However, the immune response caused by ECM, such as DNA, α-Gal epitope, or residual glutaraldehyde [36,37],…”
Section: Discussionmentioning
confidence: 99%
“…Glutaraldehyde cross-linked BHVs are liable to be calcified after being implanted into patients. Although the mechanism of in vivo calcification was not yet completely understood, it was reported that postoperative valvular calcification might be related to topical inflammatory reactions provoked by the cytotoxicity of GLUT and the affinity toward calcium of residual aldehyde groups within BHVs . Unlike GLUT, DHBA has been proved to have an anti-inflammatory effect. The experiment results revealed that the anticalcification performance of DHBA-PP was improved compared to GLUT-PP, which might be related to the reduction in the affinity to calcium of quinone oxidized from a portion of catechol …”
Section: Discussionmentioning
confidence: 99%